Effect of ventilated workwear and working schedule on physiological and psychological responses of construction workers, no. 2: Actual investigation at an active construction site. Issue 1 (27th August 2020) - Kuwabara, Kouhei; Yamazaki, Keita; Suga, Shigeo; Kobayashi, Koichiro; Hamada, Yasuhiro; Takahashi, Nao
Abstract: Although the use of cooling garments to prevent heat disorders has been increasing, the effectiveness of such garments at construction sites (CSs) remains underexplored. We investigated the relationship between the thermal environment at a CS and the physiological and psychological responses of workers wearing/not wearing ventilated work wear (VWW). The study participants were rebar placers and form workers employed at an outdoor CS. The thermal environmental conditions and the physiological and psychological responses of the workers were measured. The overall, chest, and forearm skin temperatures of the workers not wearing VWW were significantly higher than those of workers wearing VWW. To clarify the effects of VWW and working schedules on body weight loss (BWL), the BWL rate was simulated based on the evaporation rate according to a regression formula of measured data in an artificial chamber. The BWL during the late shift was higher than that in the early shift, causing dehydration in the afternoon. To prevent this condition, more water intake is required during the late shift. Abstract : The authors investigated the relationship between the thermal environment at a construction site and the physiological and psychological responses of rebar placers/form workers wearing/not wearing ventilated work wear (VWW). The overall, chest, and forearm skin temperatures of the workers not wearing VWW were significantly higher than those of workers wearing VWW. Increased body weight loss during the late shift compared with the early shift caused dehydration in the afternoon.